COMPARATIVE STUDY OF CARBON EMISSION AND PRICE ON THE ALTERNATIVES OF BUILDING WALL CONSTRUCTION - Azmi, Arsyad; Fawaza, Wirawan; Ariyuda, Bratha (Built Environment Studies, 2024)
The Indonesian government wants to meet the demand for housing by increasing housing development. However, the increase in housing development also contributes to a large percentage of carbon emissions. Therefore, it is necessary to evaluate autoclaved aerated concrete (AAC), a commonly used wall material, and precast sandwich panels (PSP), which have low emissions. The research was conducted to determine how the two materials compare prices to meet housing needs and emission reduction goals. The study is carried out by its price to meet the demand target and Life Cycle Assessment (LCA) to meet the emission reduction target. The subject of the study is one of a complex of 40 types of house buildings. Their wall construction cost and transportation cost determine the price. LCA approached the method with a cradle-to-handover framework, which is used to identify the carbon embodiment of a building. The results show that PSP walls cost 53.30% more to build than AAC walls but produce 37.20% less carbon emissions. The highest emissions occur during the production/manufacturing phase. Future studies could adopt a cradle-to-grave LCA framework to provide a more comprehensive assessment.